Quality of public finances and growth - António Afonso; Werner Ebert; Ludger Schuknecht; Michael Thöne (European Central Bank (ECB), 2005)
In this paper we review the linkages between the quality of public finances, that is, the level and composition of public expenditure and its financing via revenue and deficits, and economic growth. We review the various channels through which public finances affect growth and its underlying determinants (institutional framework, employment, savings and investment, innovation). The paper addresses the approaches used to assess the performance and efficiency of public spending, and surveys the empirical findings on the impact of fiscal variables on sustained economic growth.
Keywords: H50; O40; 330; Efficiency; Growth; quality of public finances; Öffentliche Finanzen; Steuer; Wirtschaftswachstum; OECD-Staaten; Wirkungsanalyse